Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division terhadap Hasil Belajar Siswa SMK Negeri 2 Bojonegoro - Prayogi Laksono Ariadi; Desy Ratna Arthaningtyas (Jurnal Pendidikan Indonesia, 2026)
This article assesses how Student Team Achievement Division (STAD) functions in vocational construction learning and compares the student achievement obtained through STAD with Project Based Learning (PjBL). The study also records students' responses to the use of STAD in the Basic Construction subject, Soil Surveying Element, at SMK Negeri 2 Bojonegoro. A quasi-experimental design was applied using a Non-Equivalent Control Group. The experimental class received STAD, while the control class received PjBL. Data came from pretest and posttest scores and from a student response questionnaire. The posttest scores were analyzed with the Independent Sample t-Test in SPSS after the prerequisite tests were met. Validation results placed the learning tools and research instruments in the very feasible category. Student responses to STAD also reached the very good category. The posttest comparison produced Sig. (2-tailed) = 0.477, which exceeded 0.05. This result led to the acceptance of H0 and the rejection of Ha. Therefore, STAD did not produce learning outcomes that differed significantly from PjBL. Both models showed similar effectiveness for the topic studied, although STAD had not shown a statistically significant advantage in cognitive achievement.